Kepemimpinan Dalam Islam (Sebuah Pendekatan Normatif) - Khairuddin Khairuddin; Ali Murtopo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2022)
Religion is the truth that comes from God, and religion has the value of the ultimate. It is only God who knows the truth, and he is the only one who understands the truth. Through the library study approach, there are various leaders in Islam, including the words Khalifah, Ulil Amri, Imam, and Ro’in. There are two forms of people's paradigms of Islamic leadership: the formalistic paradigm and the substantive paradigm. It is not only God’s will, but it is also His will, and it is His will that he will be the Lord of all the worlds. The ideal leader according to the Islamic concept is a leader who practices the basic principles of leadership in Islam, such as the principle of Tauhid (QS.an-Nisa:48, QS.al-Ikhlas:1-4), the principles of Mutyawarah (Qs. al-Imran:159), the principles of justice (QC.an-Nisa:58, QC.al-Maidah:8), the principle of equality (QD. Al-Huzarat:13), and the principle of responsible freedom. (QS.al-Baqarah:256, QS.al-Kahfi:29). In addition to the above principles, an ideal leader is one who has leadership like what has been explained by the Prophet (peace be upon him), because in him there is a good teaching, which is reflected in the nature or character of the prophet (Siddik), Tabligh (delivering the truth), Trust (believing), and Fathannah.